What Drives Private Sector Exit from Infrastructure? Economic Crises and Other Factors in the Cancellation of Private Infrastructure Projects in Developing Countries - Harris, Clive; Pratap, Kumar V. (World Bank, Washington, DC, 2012)
The private sector exits only a fraction of private infrastructure projects before the contract ends. Yet such cancellations can have a sustained impact on a country's program of public-private partnerships, reducing the private sector's confidence in the government's commitment as well as the government's confidence in the robustness and "value for money" of these arrangements. Econometric analysis shows that macroeconomic shocks nearly double the cancellation rate. As today's global financial crisis greatly increases the cost, and reduces the availability, of project financing, the number of cancellations could grow. That would have implications for the role public-private partnerships can play in meeting the infrastructure needs of developing countries.